A Hepatocyte‐Mimicking Antidote for Alcohol Intoxication. Issue 22 (11th April 2018) - Xu, Duo; Han, Hui; He, Yuxin; Lee, Harrison; Wu, Di; Liu, Fang; Liu, Xiangsheng; Liu, Yang; Lu, Yunfeng; Ji, Cheng
Abstract: Alcohol intoxication causes serious diseases, whereas current treatments are mostly supportive and unable to remove alcohol efficiently. Upon alcohol consumption, alcohol is sequentially oxidized to acetaldehyde and acetate by the endogenous alcohol dehydrogenase and aldehyde dehydrogenase, respectively. Inspired by the metabolism of alcohol, a hepatocyte‐mimicking antidote for alcohol intoxication through the codelivery of the nanocapsules of alcohol oxidase (AOx), catalase (CAT), and aldehyde dehydrogenase (ALDH) to the liver, where AOx and CAT catalyze the oxidation of alcohol to acetaldehyde, while ALDH catalyzes the oxidation of acetaldehyde to acetate. Administered to alcohol‐intoxicated mice, the antidote rapidly accumulates in the liver and enables a significant reduction of the blood alcohol concentration. Moreover, blood acetaldehyde concentration is maintained at an extremely low level, significantly contributing to liver protection. Such an antidote, which can eliminate alcohol and acetaldehyde simultaneously, holds great promise for the treatment of alcohol intoxication and poisoning and can provide therapeutic benefits. Abstract : A hepatocyte‐mimicking antidote for alcohol intoxication is developed by codelivering the nanocapsules of alcohol oxidase, catalase, and aldehyde dehydrogenase to the liver. This approach can effectively reduce the blood alcohol and acetaldehyde concentration, minimize liver injuries, and be readily translated as an effective antidote for alcohol intoxication.